Molecular Characterization of Native Isolates of Metarhizium rileyi (Farlow) Samson (Ascomycetes: Hypocreales) from Major Cropping Ecosystems of Northeastern Karnataka, India - , Mamatha M; , Arunkumar Hosamani; , Hanchinal S G; , Vijaykumar N. Ghante; , Aswathanarayana D S; Bhuvaneshwari,; , Prashanth G. (Archives of Current Research International, 2024)
Aims: In India, commercial biopesticides have been recommended against different insect pests on different crops, but their application has shown only a reduced efficiency attributed to differences in susceptibility of target insect pests or non-adaptability to Indian agro-climatic conditions. Therefore, there is a need to isolate region-specific biopesticide strains to enhance the efficacy of such biopesticides for pest management. The current study aimed to explore the new isolates of the entomopathogenic fungus, Metarhizium rileyi (Farlow) Samson species across the major cropping ecosystems of kalyana Karnataka. M. rileyi is an important entomopathogenic fungus of more than 30 species of Lepidoptera larvae. The aim of this research was to characterize the isolate of M. rileyi from Northeastern Karnataka by using morphological and molecular approaches. Methodology: The fungus was isolated from the naturally infected cadavers collected from different cropping ecosystems and it was cultured on Sabouraud’s Maltose Yeast Extract Agar (SMAY) media for morphological characterization, SMY media used for molecular characterization. The vegetative hyphae of fungi were 2-3 µm in diameter and hyaline, septate. The conidia ellipsoidal, smooth, and pale green were observed under the optical microscope. The DNA was isolated using the CTAB method and an internal transcribed spacer (ITS1, ITS4) was used as the primers for the amplification. The amplified products of 650 bp were purified and sequenced at ClustaL W in both directions using the above primers. A consensus sequence was obtained by alignment of the forward and reverse sequences for this region and deposited in GenBank (UASRBC Mr-24, UASRBC Mr-3, UASRBC Mr-20, UASRBC Mr-29, UASRBC Mr-7, UASRBC Mr-18). Result: A BLAST search of the sequence in GenBank revealed a 50-100 percent identity with several strains of M. rileyi (Eg. JQ686668, MN907775 and KJ725726 etc.,). Conclusion: The phylogenetic relationship was derived from comparisons of the ITS gene sequences and a Dendrogram was constructed. The homology and variations based on amino acid sequences among the isolates showed 71 per cent (OK184897) and 51 per cent similarity with four isolates (OK184899, OK177835, OK178862 and OK184898).